Perancangan Sistem Informasi Simpan Pinjam Berbasis Web Dengan Metode Waterfall (Studi Kasus : Koperasi Mitra Karya Manunggal) - Achmad Maulana; Maulana Ardhiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
During the current pandemic, activities are needed to move the community's economy, including the form of a Savings and Loans Cooperative (KSP) business entity, in this case the Mitra Karya Manunggal savings and loan cooperative. The basis of this activity is good, fast, precise and accurate service to cooperative members, cooperative management and other related parties, so an information system that meets these criteria is needed. The design of a web-based information system uses the waterfall method based on input analysis of the current system which produces an output of a proposed system analysis that integrates data in a database, fast data processing, storage security and easy data access for users. Technical data design begins with the creation of UML (Unfield Modeling Language) and development is carried out using the Waterfall method from the stage of system requirements analysis, design, coding, testing, and maintenance are completed sequentially so as to produce an information system that suits your needs.